Mining for gold and finding only nuggets: attempting a rapid systematic review, on trust in higher education IBL classrooms. Issue 1 (19th May 2021) - Beltrano, Natalie R.; Archer-Kuhn, Beth; MacKinnon, Stacey
ABSTRACT: It is well-documented throughout the available literature that trust, or a leap of faith, plays a key role in facilitating success in student learning. In this study, we attempted a rapid systematic review of relevant databases looking for studies that addressed developing and maintaining trust among students, between students and their professors, within higher education institutions, paying particular attention to inquiry-based learning practices where taking intellectual risks is key. Our efforts revealed that there are currently no empirical studies that link risk and trust in early engagement in higher education IBL (i.e., IBL-HE) classrooms. Though the 'gold mine' remained out of reach, our secondary review uncovered several important nuggets which confirmed our belief that this is an important area of future inquiry and allowed us to identify barriers to trust and note student fears. Further research is required to examine the factors that promote risk-taking and trust development and the relationship with early engagement in IBL-HE courses.